Effectiveness of an integrated-weight management programme in reducing body weight among noncommunicable disease patients in Malaysian government primary care clinics - Tan, Siew Tin (2021)
Worldwide, there were 1.3 billion (26%) adults aged 18 years old and above were overweight in 2016. More than 650 million (13%) adults were obese. In Malaysia, it was reported that the prevalence of overweight was 30.4% whilst the prevalence of obesity was 19.7% in 2019. Obesity could lead to noncommunicable diseases (NCDs) and other complications. This study aimed to develop, implement, and evaluate a new integrated-Weight Management Programme (i-WMP) in reducing body weight (BW) as the primary outcome among NCD patients in Malaysian government primary care clinics. A randomised, single-blind, parallel-group trial study was carried out in two Malaysian government primary care clinics (Hulu Langat District, Selangor). Two hundred forty-four eligible patients were invited, consented, recruited, and randomised into intervention (n = 122) or wait-list control group (n = 122). Behaviour change wheel (BCW) was used as the theoretical framework to develop the i-WMP. This i-WMP consisted of three sessions. Session 1 and 2 were implemented at week 0 and Session 3 was implemented at week 4. The baseline data were collected using validated, pre-tested, and self-administered questionnaires. These questionnaires included information on socio-demographic profile; smoking and vaping; anthropometric measurements such as BW, body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR), body fat percentage (BF%); knowledge, attitude, and practice (KAP) towards dietary and physical activity; total physical activity metabolic equivalent of task (MET)-minutes/week and sitting time (International Physical Activity Questionnaire short form, IPAQ-SF); depression (Patient Health Questionnaire, PHQ-9); anxiety (The Generalised Anxiety Disorder Scale, GAD-7). Data collected were analysed using the application of IBM SPSS (version 23). The generalised linear mixed model was performed for programme evaluation. The confidence interval was set at 95% and a level of significance of 0.05. Once randomised, all participants were included in the analysis, intent-to-treat principle was applied for lost follow-up. The retention rate was 74.2%. Results exhibited that the i-WMP was effective in reducing BW (F (2, 499) = 16.020, p < 0.001), BMI (F (2, 499) = 16.711, p < 0.001), WC (F (2, 499) = 16.767, p < 0.001), WHtR (F (2, 499) = 16.918, p < 0.001), and total sitting time (F (2, 499) = 3.774, p = 0.024). This programme also was effective in improving diet knowledge (F (2, 499) = 6.134, p = 0.002), diet attitude (F (2, 499) = 10.201, p < 0.001), diet practice (F (2, 499) = 43.080, p < 0.001), physical activity knowledge (F (2, 499) = 34.527, p < 0.001), physical activity attitude (F (2, 499) = 19.252, p < 0.001), and physical activity practice (F (2, 499) = 12.455, p < 0.001). Nonetheless, the changes in BF% and total physical activity MET-minutes/week did not reach statistical significance. i-WMP is effective in reducing BW, BMI, WC, WHtR, and total sitting time; while improving KAP towards dietary and physical activity in these patients with NCD. This i-WMP could be recommended and implemented in the primary care setting.